Claim for Costs Due to Rerouting of SUTT 150 kV New Garuda Sakti – Perawang - Wesleyzon Sitompul; Sami'an, Sami'an; Hardjomuljadi, Sarwono (International Journal of Law Policy and Governance, 2025)
Purpose –This study aims to analyze the impact of design changes from lattice tower to steelpole on the 150 kV New Garuda Sakti - Perawang electricity transmission project, with a focus on legal and financial implications, including cost claims, material efficiency, and land acquisition. Methodology/approach –This study uses a qualitative approach with analysis of contract documents, applicable legal regulations, and technical data related to the project. Additional data were obtained through a literature review of relevant regulations, such as Presidential Regulation No. 16 of 2018 and Law No. 2 of 2017, as well as the international standard FIDIC Conditions of Contract. Findings –The design change from lattice tower to steelpole provides material efficiency because it utilizes waste material without new procurement. The use of land owned by the road eliminates the need for land acquisition, but there are additional costs arising from the adjustment of installation and labor. From a legal perspective, claims for additional costs are acceptable if they are in accordance with the contract and supported by valid documentation.. Novelty/value –Given the importance of cost claims management and legal compliance in infrastructure projects, this research provides important insights for construction industry players in managing design changes and legal challenges.